Carotid intima-media thickness and C-reactive protein in patients with abdominal obesity - O. D. Belyaeva; A. V. Berezina; E. A. Bazhenova; V. Mandal; N. I. Ananyeva; O. A. Berkovich; E. I. Baranova; Е. V. Shlyakhto (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To assess atherosclerosis severity by duplex ultrasound of common carotid arteries (CCA), as well as C-reactive protein (CRP) levels, in 30-55-year-old patients with abdominal obesity (AO).Material and methods. The study included 203 patients (mean age 45,9+0,5 years) — 152 women (mean age 45,9+0,8 years) and 51 men (mean age 44,4+1,5 years) with AO (waist circumference, WC, >80 cm in women, >94 cm in men). In total, 36,5% were overweight (body mass index, BMI, 28,0+0,2 kg/m2), and 63,5% were obese (BMI 35,1+0,5 kg/ m2). All participants underwent duplex CA ultrasound (ALOKA SSD-3500, Japan); CRP level was measured by quantitative turbidimetry.Results. In AO patients, early CA atherosclerosis and increased CRP level were observed. Atherosclerotic plaques in CCA and/or internal CA were found in 39,8%. CCA intima-media thickness (IMT) correlated with WC and insulin level. CRP concentration positively correlated with IMT insulin level, WC, BMI, and negatively correlated with highdensity lipoprotein cholesterol.Conclusion. In AO patients aged over 30 years, duplex CCA ultrasound should be recommended for early atherosclerosis diagnostics.